ИННОВАЦИОННЫЕ МЕТОДЫ КОРРЕКЦИИ СЛУХОВЫХ ПРОСТРАНСТВ - Саламова, Ф.Х. (SCIENCE and SOCIETY, 2025)
Preschool sign language teaching is a multifaceted and interdisciplinary field that requires an integrated approach. The connection with medicine, psychology, linguistics and pedagogy makes it possible to create an effective educational environment for children with hearing impairments.